Stimulation of the immune system by liposomes with potassium orotate (review) - V. V. Mosyagin (Аграрная наука Евро-Северо-Востока, 2023)
The review article analyzes the existing world experience in obtaining liposomes for targeted delivery of a medicinal substance potassium orotate to tissue macrophages to stimulate the immune system. The selection of literary sources was carried out on the basis of the relevance of the information and the depth of the research. It has been established that liposomes are nanocontainers, vesicles (vacuoles) formed by a two-layer lipid membrane in the inner space of which the active medicinal substance is enclosed. Liposomes are used in medicine, veterinary medicine and cosmetology for targeted delivery of substances to target cells. They can be obtained by convection method as well as the method of voicing, the method of dissolution and removal of detergent, the method of evaporation with phase reversal, etc. The search and analysis of literature sources and patent database showed that injection method and manual shaking method are widely used methods of liposome production. Another promising means of delivering active components are niosomes – vesicles based on surface-active substance. To obtain niosomes, the method of processing solutions in an ultrasonic disintegrator is used. The well-known immunostimulating agent potassium orotate was chosen as the active substance. The target cells for liposomes are tissue macrophages as the initial link in the immunological chain. In particular, they perform an antigen-presenting function, secrete a number of cytokines, etc. Testing of a drug containing liposomes with encapsulated potassium orotate in experiments on rats and pigs showed its high regenerative ability, antibacterial activity and anti-inflammatory effect. Based on the literature data, a scheme of action of liposomes with encapsulated potassium orotate is proposed.